Estimated Glomerular Filtration Rate Trajectories in HIV-Infected Subjects Treated With Different Ritonavir-Boosted Protease Inhibitors and Tenofovir Disoproxil Fumarate or Abacavir. Issue 22 (May 2016) - Gianotti, Nicola; Galli, Laura; Poli, Andrea; Salpietro, Stefania; Nozza, Silvia; Carbone, Alessia; Merli, Marco; Ripa, Marco; Lazzarin, Adriano; Castagna, Antonella
Abstract : Abstract: The aim of the study was to evaluate in human immunodeficiency virus (HIV)-infected patients estimated glomerular filtration rate (eGFR) trajectories during treatment with different protease inhibitors (PIs) or a non-nucleoside reverse transcriptase inhibitor (NNRTI) plus tenofovir (TDF) or abacavir (ABC) and lamivudine or emtricitabine (xTC). Retrospective study of patients followed at a single clinical center; all patients who started TDF or ABC for the first time with a NNRTI or lopinavir/r (LPV/r) or atazanavir/r (ATV/r) or darunavir/r (DRV/r), for whom at least 1 eGFR value before the start and during the studied treatment was known, were included in this analysis. eGFR was calculated by means of the CKD-EPI formula. Univariate and multivariate mixed linear model (MLM) was applied to estimate eGFR slope with the considered antiretroviral treatment. In the 1658 patients treated with TDF/xTC (aged 43 [37–48] years, with an eGFR of 105 [96; 113] mL/min/1.73 m 2, 80% males, 92% Caucasians, 10% coinfected with HCV, 4% with diabetes, 11% with hypertension, 38% naive for antiretroviral therapy (ART), 37% with HIV-RNA <50 copies/mL) the median follow-up was 2.5 (1.2–4.6) years. Their adjusted eGFR slopes (95% CI) were −1.26 (−1.58; −0.95), −0.43 (−1.20; +0.33), −0.86 (−1.28; −0.44), and −0.20 (−0.42; +0.02) mL/min/1.73 m 2 per year in patients treated with ATV/r, DRV/r, LPV/r, and NNRTI, respectively. Patients receiving ATV/r or LPV/r had a greater adjusted decline in eGFR compared with those receiving NNRTIs (difference −1.06 [−1.44; −0.69] mL/min/1.73 m 2 per year, P  <0.001; and −0.66 [−1.13; −0.20] mL/min/1.73 m 2 per year, P  = 0.005, respectively); adjusted eGFR slopes were similar in patients receiving DRV/r and in those receiving NNRTIs. Patients receiving ATV/r had a greater adjusted eGFR decline than those treated with DRV/r (difference −0.83 [−1.65; −0.02] mL/min/1.73 m 2 per year; P  = 0.04), but not than those receiving LPV/r; no significant difference was observed in adjusted eGFR slopes between patients receiving DRV/r and those receiving LPV/r. In the 286 patients treated with ABC and lamivudine, eGFR slopes were similar, independent of the PI. In patients receiving TDF/xTC, eGFR trajectories were small for all regimens and declined less in patients receiving DRV/r or NNRTIs than in those treated with ATV/r or LPV/r.